Microbial degradation and watershed weathering jointly regulate soil organic matter stabilization in alpine wetlands - Bin Niu; Tianzhu Lei; Qiuyu Chen; Yilun Hu; Hailiang Dong; Yibo Yang; Jizhong Zhou; Gengxin Zhang (Communications Earth & Environment)
Abstract Wetland soils store more organic carbon than upland soils, yet the role of catchment weathering in shaping soil organic matter remains underexplored. Here, we investigated how short-term biological and long-term weathering processes influence organic matter stabilization across an alpine wetland gradient on the Tibetan Plateau, spanning different temperatures and weathering regimes. We found that free particulate organic matter increased with mean annual temperature and was linked to plant and microbial activity. In contrast, heavy particulate organic matter and mineral-associated organic matter accumulated with increasing weathering intensity, and their stabilization was promoted through reduced microbial decomposition by metal-binding, particularly involving calcium. These findings were further supported by a global meta-analysis of 316 paired wetland soil samples, confirming the positive relationships among weathering, calcium content, and organic matter storage. Our results highlight the need to integrate weathering and microbial functions into soil carbon models in alpine wetlands responding to climate warming.